Role of exosomes and exosomal microRNA in muscle–Kidney crosstalk in chronic kidney disease - Zhou, Sijie; Cheing, Gladys Lai Ying; Cheung, Alex Kwok Kuen (Frontiers in Cell and Developmental Biology, 2022)
Chronic kidney disease (CKD) is a progressive damage of kidneys that can no longer serve the blood-filtering function, and is a life-threatening condition. Skeletal muscle wasting is a common complication of CKD. Yet the relationship between kidney and skeletal muscle in CKD remains unclear. Exosomes, a type of small membrane-bound vesicles released from cells to the extracellular environment, have increasingly received attention due to their potential as mediators of crosstalk between kidneys and different organs, including skeletal muscle. This mini-review summarizes the recent findings that point to the role of exosomes in the cross-talk between kidney and skeletal muscle in CKD. Understanding of the contents and the mechanism of exosome release may prone exosomes be the potential therapeutic targets for CKD.